2019
DOI: 10.1371/journal.pone.0225704
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic group behaviour II: On the dependence of triad spatial dynamics on social and personal features; and on the effect of social interaction on small group dynamics

Abstract: In a follow-up to our work on the dependence of walking dyad dynamics on intrinsic properties of the group, we now analyse how these properties affect groups of three people (triads), taking also in consideration the effect of social interaction on the dynamical properties of the group. We show that there is a strong parallel between triads and dyads. Work-oriented groups are faster and walk at a larger distance between them than leisure-oriented ones, while the latter move in a less ordered way. Such differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…However, a more formal analysis is beyond the scope of the present paper but should be considered in future work. The interested reader is also pointed to relevant work on group behavior within the context of pedestrian dynamics (e.g., 55 60 ).…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…However, a more formal analysis is beyond the scope of the present paper but should be considered in future work. The interested reader is also pointed to relevant work on group behavior within the context of pedestrian dynamics (e.g., 55 60 ).…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The typical walking speed of pedestrians is very important in transport, as it directly determines the flow through facilities or the egress time in evacuations. Previous work suggests that group speed decreases with social group size [26], but others suggest that the speed of triads is larger than the speed of dyads and that the speed of individuals is higher than that of social groups, additionally depending on the walking purpose [27] or even gender [28]. The spatial structure adopted by social groups appears to arise from a trade-off between maintaining cohesion and facilitating communication against the need to avoid collisions with other pedestrians.…”
Section: Introductionmentioning
confidence: 96%
“…For example, group members walk next to each other at low densities to facilitate communication and adopt more compact patterns (V-shaped or U-shaped patterns) to avoid conflicts with other pedestrians [9,29]. In addition, group structures are affected by other factors, such as the relation between group members and the gender of the group members [27,28]. Considering the space maintained by and around social groups, some authors indicate that larger social groups require more space per person than smaller groups [21].…”
Section: Introductionmentioning
confidence: 99%
“…Turgut et al [22] proposed a social force model to study pedestrian group behavior during evacuation and found that the groups with leaders result in less evacuation time than groups without leaders. Zanlungo et al [23], [24] pointed out that the small groups would display some robust features during walking, respectively a tendency to walk abreast for dyads, in a V-shape for triads, in a U-shape for groups of 4 and 5 members, as well as a reduced speed on average compared to individuals.…”
Section: Introductionmentioning
confidence: 99%